Regional Business Cycles in East Asia: Synchronization and its Determinants - Young-Joon Park (East Asian Economic Review, 2013)
This paper analyzes the dynamics and nature of regional business cycle synchronization for East Asian countries in the period of 2000:Q1-2011:Q4. Estimating a dynamic two-factor model extracts the common factor and the nation- specific factor from both the macroeconomic aggregates and plausible driving forces of regional business cycles. Evidence for regional business cycle synchronization is particularly strong for Korea, Malaysia and the Philippines, while Japan shows weak evidence of regional synchronization. On the other hand, Indonesia, Thailand, Singapore and China are decoupling from regional business cycles. The driver of monetary aggregate is the most significant determinant of regional fluctuations of macroeconomic aggregates, whereas oil price and productivity are on average important driving forces of nation-specific fluctuations of real economic activities.